A mitotic form of the Golgi apparatus in HeLa cells (The Rockefeller University Press, 1987)
Galactosyltransferase, a marker for trans-Golgi cisternae in interphase cells, was localized in mitotic HeLa cells embedded in Lowicryl K4M by immunoelectron microscopy. Specific labeling was found only over multivesicular structures that we term Golgi clusters. Unlike Golgi stacks in interphase cells, these clusters lacked elongated cisternae and ordered stacking of their components but did comprise two distinct regions, one containing electron-lucent vesicles and the other, smaller, vesiculo-tubular structures. Labeling for galactosyltransferase was found predominantly over the latter region. Both structures were embedded in a dense matrix that excluded ribosomes and the cluster was often bounded by cisternae of the rough endoplasmic reticulum, sometimes on all sides. Clusters were present at all stages of mitosis examined, which included prometaphase, metaphase, and telophase. They were also identified in conventionally processed mitotic cells and shown to contain another trans-Golgi marker, thiamine pyrophosphatase. Serial sectioning showed that clusters were discrete and globular and multiple copies appeared to be dispersed in the cytoplasm. Their possible role in the division of the Golgi apparatus is discussed.